Political risk insurance and bilateral investment treaties: a view from below - Lauge Skovgaard Poulsen (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2010)
The author reviews evidence from a survey of political risk insurance providers on the consideration of bilateral investment treaties when assessing the risk of investment projects. He finds that, while BITs are basically aimed at reducing the risk of investing abroad, many agencies that price the risk of foreign investments rarely take them into account.
Keywords: 330